Spatial Revolution : Architecture and Planning in the Early Soviet Union - Crawford, Christina E. (Book collections on Project MUSE., 2022)
"This book explores the foundations of early Soviet architecture and planning in a narrative arc across vast geography. The book binds together three industrial-residential projects in Baku, Magnitogorsk, and Kharkiv, built during the first fifteen years of the Soviet Union, that became living laboratories to test socialist spatial models"--